NAUJOSIOS MEDUOS KAIP KLASIKINĖS UGDYMO PARADGIMOS ALTERNATYVA. - Klibavičius, Darius (Problems / Problemos, 2013)
the article focuses on the new media-based edu- cation as an alternative to the classical paradigm of education initiated by print culture. Ttherefore, the controversy between two media philosophy models is analysed here. One of these models refers to phonetic writing as a paradigmatic innovation which appeared in the Antiquity, while the other one is related to the emergence of electronic media in the Contemporary Age. Although the oral tradition was replaced by writing and handwriting culture by print, similarly the domination of the printed word is being displaced by the new electronic and digital media, each of these communication technologies is treated as a vastly important qualitative extension of the previous one. Thus, the article aims to answer the question of how these transformations have affected the teaching and learning environment, the learning process and students' sensory experience. While the antique education system was focused on the development of personality and the issues of reasons and causes, the Contemporary Age pays a lot of attention to the structures of electronic information as well as to the reflection of their consequences and effects.